Genomic and transcriptomic analysis of Saccharomyces cerevisiae isolates with focus in succinic acid production - Franco-Duarte, Ricardo (2018)
Succinic acid is a platform chemical that plays an important role as precursor for the synthesis of many valuable bio-based chemicals. Its microbial production from renewable resources has seen great developments, specially exploring the use of yeasts to overcome the limitations of using bacteria. The objective of the present work was to screen for succinate-producing isolates, using a yeast collection with different origins and characteristics. Four strains were chosen, two as promising succinic acid producers, in comparison with two low producers. Genome of these isolates was analysed, and differences were found mainly in genes SDH1, SDH3, MDH1 and the transcription factor HAP4, regarding the number of single nucleotide polymorphisms and the gene copy-number profile. Real-time PCR was used to study gene expression of 10 selected genes involved in the metabolic pathway of succinic acid production. Results show that for the non-producing strain, higher expression of genes SDH1, SDH2, ADH1, ADH3, IDH1 and HAP4 was detected, together with lower expression of ADR1 transcription factor, in comparison with the best producer strain. This is the first study showing the capacity of natural yeast isolates to produce high amounts of succinic acid, together with the understanding of the key factors associated, giving clues for strain improvement.